2014
DOI: 10.1371/journal.pone.0107388
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate Increases Intracellular Calcium Levels and Enhances Growth Hormone Release from Rat Anterior Pituitary Cells via the G-Protein-Coupled Receptors GPR41 and 43

Abstract: Butyrate is a short-chain fatty acid (SCFA) closely related to the ketone body ß-hydroxybutyrate (BHB), which is considered to be the major energy substrate during prolonged exercise or starvation. During fasting, serum growth hormone (GH) rises concomitantly with the accumulation of BHB and butyrate. Interactions between GH, ketone bodies and SCFA during the metabolic adaptation to fasting have been poorly investigated to date. In this study, we examined the effect of butyrate, an endogenous agonist for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 46 publications
(60 reference statements)
0
32
0
Order By: Relevance
“…Interestingly, recent studies showed that other mechanisms were found to interpret the function of SCFA like NaB on energy metabolism based on G-protein coupled receptors (GPCR). Miletta MC et al found that NaB increased intracellular calcium levels and enhanced growth hormone release from rat anterior pituitary cells via GPR41 and 43 42 . Moreover, the interaction of SCFA and GPR43 modulated colitis by regulating inflammatory cytokine production in mouse mononuclear cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies showed that other mechanisms were found to interpret the function of SCFA like NaB on energy metabolism based on G-protein coupled receptors (GPCR). Miletta MC et al found that NaB increased intracellular calcium levels and enhanced growth hormone release from rat anterior pituitary cells via GPR41 and 43 42 . Moreover, the interaction of SCFA and GPR43 modulated colitis by regulating inflammatory cytokine production in mouse mononuclear cells 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the transporter is likely related to the direction of energy supplies to tissues during fasting. Moreover, Miletta and colleagues found that butyrate enhances growth hormone (GH) secretion in pituitary cells via GPR41/43 activation and intracellular accumulation of Ca 2+ (131). This leads to the hypothesis that butyrate acts as a secondary mediator of metabolic adaptations of GH during fasting, which mainly include increased lipolysis and protein retention.…”
Section: Scfas and Neuronsmentioning
confidence: 99%
“…Butyrate is a short‐chain fatty acid that is closely related to the ketone body β‐hydroxybutyrate in structure and function (George & Cahill, ; Shimazu et al, ). Butyrate is the principal energy source for intestinal epithelial cells, and is directly supplied by β‐oxidation (Miletta et al, ). In addition, TB supplementation improves the level of lipase and trypsin in piglets (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%